Resilience in older people: a concept analysis - Lima, Gabriella Santos (2023)
(1) Background: Resilience has been presented as a potential protective factor to be promoted in difficult experiences in older people. However, further clarification of the concept of resilience for this population is required, as this is of critical interest for nursing care. (2) Aim: To develop the concept of resilience in older people to establish the elements that refer to the nursing outcome. Personal resilience (1309) from the Nursing Outcomes Classification (NOC), specifically in older people. (3) Methods: Concept analysis using Beth Rodgers’ evolutionary model. The attributes, antecedents, consequents, and empirical elements were described in the integrative review, with searches in PubMed, CINAHL, PsycINFO, LILACS, and Embase databases. A total of 2431 citations have been identified, and 110 studies were included. (4) Results: The concept of “resilience in older people” is composed of two attributes, available resources and positive behaviors, and is defined as positive attitudes of older people with the assistance of resources available from experiences of adversity. Conclusion: This analysis and concept development of resilience in older people provided sensitive indicators for nursing care in the context of adversity, considering available resources and with positive attitudes during this phase of life span.